Análisis sobre los riesgos de los créditos otorgados por la cooperativa de ahorro y crédito Manantial de Oro Ltda., del cantón Mejía provincia de Pichincha en el año 2011 - Guevara Lema, Martha Viviana (2013)
In recent years the number of Credit Unions in Ecuador has increased significantly, becoming an alternative development tool for the popular sector. In January 10, 2007 was formed the Cooperativa de Ahorro y Crédito Manantial de Oro Ltda. as an institution that seeks progress of the community in cultural and social, through lending to its members. This research showed the risks to which it is exposed in order to establishing the mechanisms to identify, analyze and manage adequately the economic resources at Credit Union, so the researcher reviewed information concerning to the topic in books, web pages, documents of the Credit Union, which allowed to understand and know the beginning of the Credit Union and how it has developed economically from it was created, to take better development in research, surveys were applied to savers account at Credit Union to identify their needs and how the institution helped to them, in the same way interviews were applied managers to establish their criteria about administrative and financial management of the Credit Union, the research concluded that must perform an update manual to the functions and these should be disseminated to all staff.